Libertarian paternalistic instruments fostering sustainable energy consumption: An analysis based on energy-efficient LED technology - Bianca Blum; Julian Hübner; Harald Berger; Karl Justus Bernhard Neumärker (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2018)
[Introduction ...] The focus of this paper is the analysis of the extent to which the "energy efficiency gap" can be closed with the help of this new behavioral economic approach. The light-emitting diode (LED) will be the main subject of the investigation, as it is extremely energy efficient, relatively cheap, and the change to LED bulbs is technically very easy to implement for any household. In the next section, we will state the theory behind the libertarian paternalism and its justification. Afterwards, several libertarian paternalistic instruments will be introduced. Since the literature already contains a broad variety of such instruments, this paper will focus on those, who delivered robust results in experiments and can be linked with energy consumption. We conclude this paper in the final section with a summary of the main findings and a lookout for what is to come.
Keywords: 330